2022
DOI: 10.1021/acs.energyfuels.1c04407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transition-Metal Oxide M (M = Co, Fe, and Mn) Modification on the Performance and Structure of Porous CuZrCe Catalysts for Simultaneous Removal of NO and Toluene at Low–Medium Temperatures

Abstract: In order to satisfy the characteristics of non-power plant flue gas emissions, the reaction mechanism for the simultaneous removal of NO and toluene over different transition-metal oxide M (M = Co, Fe, and Mn)-modified porous CuZrCe catalysts was investigated at low− medium temperatures. Brunauer−Emmett−Teller analysis, transmission electron microscopy, X-ray diffraction, hydrogen temperature-programed reduction, temperature-programed desorption experiment with NH 3 , Xray photoelectron spectroscopy, and in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…32 Furthermore, the NH 3 desorption peak at lower temperature was attributed to the weak acid sites and physically adsorbed NH 3 species, and the desorption peak at higher temperature was attributed to the NH 3 species adsorbed on the mediumstrong acid sites. 60,72,73 Meanwhile, the generated low-temperature Lewis acid sites during the gas-phase sulfation could convert to Brønsted acid sites via the bond of water molecules to Lewis acid sites in the presence of H 2 O. 32,74 Based on the NH 3 -TPD spectra of the gas-phase sulfated CeO 2 -OS catalysts, it can be found that the introduction of H ), which is in accordance with the NH 3 -SCR activity.…”
Section: Properties Of Redox Ability and Surface Aciditymentioning
confidence: 80%
See 1 more Smart Citation
“…32 Furthermore, the NH 3 desorption peak at lower temperature was attributed to the weak acid sites and physically adsorbed NH 3 species, and the desorption peak at higher temperature was attributed to the NH 3 species adsorbed on the mediumstrong acid sites. 60,72,73 Meanwhile, the generated low-temperature Lewis acid sites during the gas-phase sulfation could convert to Brønsted acid sites via the bond of water molecules to Lewis acid sites in the presence of H 2 O. 32,74 Based on the NH 3 -TPD spectra of the gas-phase sulfated CeO 2 -OS catalysts, it can be found that the introduction of H ), which is in accordance with the NH 3 -SCR activity.…”
Section: Properties Of Redox Ability and Surface Aciditymentioning
confidence: 80%
“…32 Furthermore, the NH 3 desorption peak at lower temperature was attributed to the weak acid sites and physically adsorbed NH 3 species, and the desorption peak at higher temperature was attributed to the NH 3 species adsorbed on the medium–strong acid sites. 60,72,73 Meanwhile, the generated low-temperature Lewis acid sites during the gas-phase sulfation could convert to Brønsted acid sites via the bond of water molecules to Lewis acid sites in the presence of H 2 O. 32,74 Based on the NH 3 -TPD spectra of the gas-phase sulfated CeO 2 -OS catalysts, it can be found that the introduction of H 2 O or O 2 decreases the weak acid sites of CeO 2 -OS catalyst, and the co-existence of H 2 O and O 2 further enhances this reduction, indicating that the introduction of H 2 O or/and O 2 during the gas-phase sulfation is unbeneficial to the formation of weak acid sites for the sulfated CeO 2 -OS catalyst by organic COS + CS 2 at 50 °C because of their effect on reducing the formed quality of sulfates.…”
Section: Resultsmentioning
confidence: 99%
“…Selective catalytic reduction using ammonia (NH 3 -SCR) is considered the most efficient method for reducing nitrogen oxides (NO x ) in flue gas through post-treatment technology. V 2 O 5 -WO 3 (MoO 3 )/TiO 2 catalysts are widely employed in SCR technology due to their exceptional SCR activity and resistance to SO 2 . However, these catalysts do have some limitations, such as the high volatility and toxicity of V 2 O 5 , decreased catalytic efficiency at lower temperatures, and increased SO 2 oxidation at higher temperatures, among others. Consequently, the search for more environmentally friendly NH 3 -SCR catalysts with improved catalytic performance has become a crucial area of research in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Mn modification is conducive to more uniform distribution of metal nanoparticles on the surface of the support, which is conducive to enhancing the interaction between the metal particles and the support, thereby improving the activity and stability of the reaction. [45][46][47] Herein, we successfully synthesized Pt 0.6 Ni 0.4 /(MnO x ) 2 -C 3 N 4 by dispersing monodisperse PtNi nanoparticles on Mn-modified graphitic carbon nitride nanosheets via a simple molten salt method and impregnation reduction method. [1] The larger specific surface area of the support and modification of Mn provided more active sites for the loading of active components, which improved its catalytic performance for the dehydrogenation of hydrous hydrazine.…”
Section: Introductionmentioning
confidence: 99%
“…The CN nanosheets prepared by the molten salt method have a large specific surface area, which provides more active sites for the loading of metal nanoparticles and plays an important role in improving the catalytic performance of the catalyst. Mn modification is conducive to more uniform distribution of metal nanoparticles on the surface of the support, which is conducive to enhancing the interaction between the metal particles and the support, thereby improving the activity and stability of the reaction [45–47] …”
Section: Introductionmentioning
confidence: 99%